2019
DOI: 10.1210/en.2019-00287
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Metabolic Impacts of Perinatal Exposure to Phthalates and Phthalate Mixtures in Mice

Abstract: Developmental exposures to phthalates are suspected to contribute to risk of metabolic syndrome. However, findings from human studies are inconsistent, and long-term metabolic impacts of early-life phthalate and phthalate mixture exposures are not fully understood. Furthermore, most animal studies investigating metabolic impacts of developmental phthalate exposures have focused on diethylhexyl phthalate (DEHP), whereas newer phthalates, such as diisononyl phthalate (DINP), are understudied. We used a longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Furthermore, alterations in hepatic acetyl-CoA and acylcarnitines were age-specific. This was consistent with our previous phenotyping studies that indicated females perinatally exposed to DEHP+DINP had increased body weight and relative liver weight at PND21, but did not exhibit these same phenotypes longitudinally ( 31 , 34 ). Additional work is needed to fully understand these complex mixture effects.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, alterations in hepatic acetyl-CoA and acylcarnitines were age-specific. This was consistent with our previous phenotyping studies that indicated females perinatally exposed to DEHP+DINP had increased body weight and relative liver weight at PND21, but did not exhibit these same phenotypes longitudinally ( 31 , 34 ). Additional work is needed to fully understand these complex mixture effects.…”
Section: Discussionsupporting
confidence: 92%
“…Females perinatally exposed to DINP exhibited the most prominent differential gene expression in the liver, and gene set enrichment analysis revealed different metabolic pathways impacted by developmental phthalate exposures in females and males. Furthermore, our previous studies indicated that females were more susceptible to long-term metabolic effects, including glucose intolerance and body fat accumulation, than males following perinatal phthalate exposures ( 34 ). In contrast, a previously published study examining liver reprogramming following developmental DEHP exposures found sex-specific reprogramming in males but not females; however, this study examined glycogen storage/depletion as the main outcome of interest, utilized higher doses of DEHP, analyzed younger mice, and only evaluated hepatic expression of one gene ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we did not observe significant changes in relative heart weights with DEHP exposure, and we did not determine the effects of DEHP exposure on cardiac function. However, we have previously demonstrated that DEHP exposure in this model results in increased body fat and decreased lean mass in adult females, 64 suggesting that this chemical has long-term, sex-specific effects on metabolic health. Moreover, adverse effects of perinatal environmental exposures may not manifest until subsequent challenges later in life, such as hormonal stimulation, poor diet, or additional environmental exposures.…”
Section: Discussionmentioning
confidence: 72%